A geographic information system (GIS) and multi-criteria analysis for sustainable tourism planning - Aminu, Mansir (2007)
The need for a sustainable approach in tourism development is very often addressed among the academia, the authorities and the stakeholders, as well as the apparent need for tools which will guide the decision environment in evaluation and planning. This project aims to identify conservation and compatible areas for tourism development in Johor Ramsar site, using spatial modeling in Geographic Information System (GIS). The study describes a methodological approach based on the integrated use of Geographic Information System (GIS) and Multi Criteria Decision Model (MCDM) to identify nature conservation and development priorities among the wetland areas. A set of criteria were defined to evaluate wetlands biodiversity conservation and development; the criteria include tree age class, harvesting season, size of endangered fauna, habitat’s proximity to natural land use/ land cover, habitat area and water quality. Having defined the criteria, the next step was selecting suitable indicators and variables to measure the selected criteria. Subsequently the criteria were evaluated from conservation and tourism development point of view. These criteria were then ranked using the pair wise comparison technique of multi criteria analysis (MCA) and the results integrated into GIS. Several conservation scenarios are generated so as to simulate different evaluation perspectives. The scenarios are then compared to highlight the most feasible and to propose a conservation and development strategy for the wetlands area. The generation and comparison of conservation and development scenarios highlighted the critical issues of the decision problem, i.e. the wetland ecosystems whose conservation and development relevance is most sensitive to changes in the evaluation perspective. This study represents an important contribution to effective decision-making because it allows one to gradually narrow down a problem.